L'analisi dell'impatto sociale generato dall'Associazione Il Mantello Ferrara/ The analysis of the social impact generated by the Association “Il Mantello”. (European journal of volunteering and community-based projects, 2024)
Purpose: The study provides an example of implementation of social impact assessment (SIA) in an association of social promotion (ASP), called Il Mantello.Methodology: To implement the SIA, a social return on investment (SROI) calculation has been performed, and the value generated by Il Mantello to its stakeholders was disclosed.Findings: The SIA was the result of a shared accountability process, to identify and satisfy the information needs of ASP’ stakeholders. Thus, a SROI report was realized thanks to the collaboration with accounting scholars of the local university, to disclose the generated social value.Practical implications: SIA realization represents a best practice. First, the SROI methodology is carefully detailed, providing indications for those third sector entities (TSEs) interested in conducting a SIA. Second, report realization places emphasis on the need for smaller TSEs to integrate external (financial and non-financial) accounting skills, to implement the SIA.Social implications: The SROI report may support the legitimacy (and survival) of the ASP in front of its stakeholders.
Keywords: social impact assessment; social return on investment; accounting; third sector entity; disclosure; stakeholders